Quantifying Central Hypotheses on Environmental Kuznets Curves for a Rich Economy: A Computable General Equilibrium Study - Annegrete Bruvoll; Taran Fæhn; Birger Strøm (Statistics Norway, Research Department, 2003)
We investigate whether the future relationships between several pollutants and per capita income in rich countries may assume the inverted U-forms of Environmental Kuznets Curves (EKC). The emission-augmenting effect of scaling up aggregate economic activity may be counteracted by greener composition of production and consumption, technological progress, and increased demand for environmental quality and policy. To quantify the importance of these central hypotheses, we use a CGE model with endogenous policy for Norway. Our results suggest significant future effects of all these three counteracting mechanisms. For most local and regional pollutants, they may be strong enough to prolong the falling emission trends. However, we cannot rely on reductions in emissions of climate gases and some transport-related local pollutants. Our results also indicate that pollution leakages abroad are likely to find place.
Keywords: D58; O11; Q25; Q28; Q48; 330; The Environmental Kuznets Curve; Endogenous Policy; Climate policy; Dynamic CGE Model.